Letter - Martinez Campillo, Juan
026-0015-001 College Victor Duruy, Bagneres de Bigorre. Hautes Pyrenees. 20th August. 1939. The Secretary, Trades Union Congress, LONDON. Dear Sir, I duly received your favour of 10th inst. and I am sorry to note that nothing immediate can be done in the matter. I thank you for your attention in the matter and hope that I may receive a reply from M. Schevenels in the near future.. In the meantime, if you should by any chance, hear of an English family who are willing to accept a Spanish proffessor "au pair", I should be very grateful if you could get into touch with me. I again thank you for all your kind attention and trust to hear from you at some later date. I remain, Yours faithfully, JUAN MARTINEZ CAMPILLO. EAB 292/946/26/15